Effect of Zirconium addition on crack, microstructure and mechanical behavior of selective laser melted Al-Cu-Mg alloy. (June 2017) - Zhang, Hu; Zhu, Haihong; Nie, Xiaojia; Yin, Jie; Hu, Zhiheng; Zeng, Xiaoyan
Abstract: Selective laser melting (SLM) was used to fabricate Al-Cu-Mg alloy and Zirconium-modified Al-Cu-Mg alloy components. The hot-cracking phenomena during the SLM process was significantly reduced by the grain refining effect caused by the addition of Zr. Compared to the Al-Cu-Mg part, the Zr-modified Al-Cu-Mg part with the ultrafine grain exhibits increased yield strength (446 ± 4.3 MPa) and ultimate tensile strength (451 ± 3.6 MPa). These findings provide a basis for innovative alloy design for SLM. Graphical abstract: